Approximate solutions to the conformable Rosenau‐Hyman equation using the two‐step Adomian decomposition method with Padé approximation. (29th October 2019) - Akgül, Ali; Aliyu, Aliyu Isa; Inc, Mustafa; Yusuf, Abdullahi; Baleanu, Dumitru
Abstract : This paper adopts the Adomian decomposition method and the Pad é approximation techniques to derive the approximate solutions of a conformable Rosenau‐Hyman equation by considering the new definition of the Adomian polynomials. The Pad é approximate solutions are derived along with interesting figures showing both the analytic and approximate solutions.